2021
DOI: 10.1080/19490976.2021.1897212
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-chain fatty acids in the interplay between gut microbiota and diet in cardio-metabolic health

Abstract: The gut microbiota plays an important role in cardio-metabolic diseases with diet being among the strongest modulators of gut microbiota composition and function. Resistant dietary carbohydrates are fermented to short-chain fatty acids (SCFAs) by the gut bacteria. Fiber and omega-3 rich diets increase SCFAs production and abundance of SCFA-producing bacteria. Likewise, SCFAs can improve gut barrier integrity, glucose, and lipid metabolism, regulate the immune system, the inflammatory response, and blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
250
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(312 citation statements)
references
References 194 publications
(253 reference statements)
5
250
0
2
Order By: Relevance
“…The diversity and composition of gut microbiota presents a greater degree of affectation in individuals who consume low-fiber diets. Alterations in the diversity and composition of the microbiota may lead to an imbalance in the production of short chain fatty acids and other postbiotics, which contributes to the proinflammatory characteristic of chronic metabolic diseases [ 58 ]. No significant results were found in Firmicutes-Bacteroidetes ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and composition of gut microbiota presents a greater degree of affectation in individuals who consume low-fiber diets. Alterations in the diversity and composition of the microbiota may lead to an imbalance in the production of short chain fatty acids and other postbiotics, which contributes to the proinflammatory characteristic of chronic metabolic diseases [ 58 ]. No significant results were found in Firmicutes-Bacteroidetes ratio.…”
Section: Discussionmentioning
confidence: 99%
“…with 60 μg/kg Anti-IL-33 neutralizing antibody (R&D Systems, Inc., Minneapolis, USA) 2 h before establishing the intestinal I/R model; ( 4 ) I/R + PA + Anti-IL-33, in which WT mice were injected i.p. with 60 μg/kg Anti-IL-33 neutralizing antibody 2 h before intestinal I/R and 2 mg/kg PA 1 h before intestinal I/R in mice; ( 5 ) I/R + PA + Anti-ST2, in which WT mice were injected i.p. with 2 mg/kg PA and 1.5 mg/kg Anti-ST2 neutralizing antibody (R&D Systems, Inc.) 1 and 2 h, respectively, before establishing the intestinal I/R model in mice.…”
Section: Methodsmentioning
confidence: 99%
“…The human intestinal commensal flora and related metabolites have always been considered factors related to the health of the host ( 4 , 5 ). We previously confirmed that intestinal I/R induces significant intestinal flora disorders and changes in metabolites and showed that intestinal flora metabolites play an important regulatory role in intestinal I/R injury ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs also play a very important role in the protection of the human body. This applies to two aspects: the first is the inhibition of histone deacetylase (HDAC) activity, and the second is the participation in signaling by the complex of free fatty acid receptors coupled with G proteins (GPRs) [ 34 , 35 ].…”
Section: The Process Of Immune Modulation By Human Gut Microbiotamentioning
confidence: 99%